Water Quality and Nitrogen Mass Loss from Anaerobic Lagoon Columns Receiving Pretreated Influent. Issue 4 (1st July 2014) - Szogi, Ariel A.; Vanotti, Matias B.
Abstract : Control methods are needed to abate NH3 losses from swine anaerobic lagoons to reduce the contribution of confined swine operations to air pollution. In a 15‐mo meso‐scale column study, we evaluated the effect of manure pretreatment on water quality, reduction of N losses, and sludge accumulation in swine lagoons using (i) enhanced solid–liquid separation with polymer (SS) and (ii) solid–liquid separation plus biological N treatment using nitrification–denitrification (SS + NDN). A conventional anaerobic lagoon was included as a control. Concentrations of total Kjeldahl N (TKN), total ammoniacal N (TAN), and NO3 –N were monitored during the course of the study, and the volumes of column liquid and sludge were used to estimate N mass flows. At the end of the study, TKN and TAN concentrations in the liquid of SS columns were 35 and 37% lower than the control, respectively, and TKN and TAN concentrations in SS + NDN were 97 and 99% lower than the control. The N mass flow analysis revealed that SS reduced total N inflow by 30% and SS + NDN by 82% compared with the control. The SS was ineffective at reducing NH3 losses compared with the control. Instead, SS + NDN effectively reduced total NH3 losses by 50%, most of which occurred during the first 6 mo of the study. Although both pretreatments can stop the mass accumulation of total N in sludge, SS + NDN had the advantage of improving water quality and abating NH3 emissions from treated lagoons. As an additional environmental benefit, SS + NDN effluents could be used for crop irrigation without the risk of NH3 losses during land application.